ANALYSIS OF OPPORTUNITIES AND ECONOMIC EFFICIENCY OF LEMON PRODUCTION IN SMALL AREAS - Rustambek Imomov (Antis Publisher, 2024)
Lemon cultivation has gained global significance, especially during the COVID-19 pandemic, as demand for immune-boosting foods surged. Lemons, rich in vitamin C and antioxidants, are increasingly valued for their health benefits. This study examines the economic efficiency of lemon farming, focusing on advanced cultivation technologies such as trench-style and film greenhouses, which are widely adopted in Uzbekistan. The research analyzes the cost-effectiveness of these methods, highlighting their ability to generate high yields even on small land areas. Findings indicate that trench greenhouses, which do not require heating systems, are twice as cost-effective as film greenhouses, making them a preferred option for farmers. A single lemon tree can produce 200-250 fruits in trench greenhouses and 400-500 fruits in film greenhouses annually. Farmers also optimize profitability by intercropping garlic in the early years of lemon cultivation, achieving steady income while waiting for lemon trees to mature. The study reveals that investment costs, including greenhouse construction, seedling procurement, and agro-technical measures, are recoverable within five years, supported by soft loans under the